Transformasi Digital Pelayanan Publik: Tantangan dan Prospek dalam Implementasi E-Government di Kabupaten Bima - Nurlaila Nurlaila; Zuriatin Zuriatin; Nurhasanah Nurhasanah (Universitas 17 Agustus 1945 Semarang, 2024)
The urgency of this research lies in the importance of digital transformation in enhancing the quality of public services in Bima Regency. This study employs a qualitative descriptive approach to explore digital transformation in public services in Bima Regency. The research subjects involve local government officials, SKPD employees, and the general public to obtain a broad perspective on the obstacles and solutions in digital transformation. The research findings indicate that the implementation of e-Government faces various significant challenges, including accessibility, digital literacy, cultural and organizational changes, official support, and budget allocation. Bima Regency requires an inclusive and affordable approach to develop e-Government services accessible to all layers of society, including those in remote areas and vulnerable groups. Digital literacy emerges as a crucial factor in confronting digital transformation, and structured digital literacy programs can assist the public and government employees in acquiring the necessary knowledge and skills. Cultural and organizational changes are also vital in adopting e-Government, necessitating organizational restructuring, capacity building, and continuous learning. Support from officials and public awareness are also crucial factors in the successful implementation of e-Government. With commitment from officials and public awareness of the benefits of e-Government, local governments can accelerate technology adoption and ensure widespread participation from all layers of society. Additionally, adequate budget allocation is crucial in supporting the development of e-Government, enabling the construction of robust technological infrastructure and enhancing service accessibility.